MANAJEMEN PARENTING IBU KARIR DALAM MEWUJUDKAN PENDIDIKAN SPIRITUAL ANAK - Cut Irhamna Heriyanti (AL-ILMU, 2021)
The problem of moral degradation of children, which is often found in this age of technology and information, can be triggered by various factors, one of which is the quality of children's spiritual education in the family. Admittedly or not, this trend poses a serious risk in efforts to maximize children's spiritual education, considering that the mother's role in children's education is more dominant than the father's role. Specifically so that the quality of children's spiritual education is not disturbed. One of them is implementing good and solid parenting management. With all the limited time, career mothers can implement this education by implementing parenting management through the stages of management functions, such as planning, organizing, actuating and controlling. These efforts are expected to be able to overcome the various negative impacts caused by the limited time mothers work in educating the spiritual aspects of children.